Analyzing the US Genetically-Modified Soybean Consumption: Its Implication in Indonesia - Zefanya Alanza Christabel Loveldy; Imas Nurzanah; Impo Philipus Sitindaon; Ira Tutia; Tondi Sudaryo (Prosiding Industrial Research Workshop and National Seminar, 2018)
Agricultural production problem causes the rising of GM food development. Indonesia, as a country with the significant amount of soybean consumption, mostly imported from the US to meet the needs of soybean consumption. As the factors that may affect the consumption, GDP, education index, and food security become the variables in this study. This paper examines the association between education, income, food security, and genetically-modified soybean consumption. Using secondary data of US from 2006-2015, the result shows a direct association between food security and GM soybean consumption. However, education and income tend not to have a significant relationship. From the results, this paper discusses the factors that associate with GM soybean consumption and its implication in Indonesia.